2009
DOI: 10.1007/s00330-009-1639-4
|View full text |Cite
|
Sign up to set email alerts
|

Large-volume multi-tined expandable RF ablation in pig livers: comparison of 2D and volumetric measurements of the ablation zone

Abstract: Two-dimensional CT measurements assuming rotational symmetry of the AZ overestimate the largest ablated sphere centred on the electrode shaft compared with 3D CT measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…This study’s results showed that the diameter-derived sphere volume was larger than the tumor volume on the basis of the assumption of rotational symmetry, which was consistent with prior findings in experimental and clinical animal studies. 37 , 38 , 39 Consequently, the spherical cut-points may facilitate the re-identification in patient subgroups that possibly benefit from locoregional or salvage therapies. 34 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…This study’s results showed that the diameter-derived sphere volume was larger than the tumor volume on the basis of the assumption of rotational symmetry, which was consistent with prior findings in experimental and clinical animal studies. 37 , 38 , 39 Consequently, the spherical cut-points may facilitate the re-identification in patient subgroups that possibly benefit from locoregional or salvage therapies. 34 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar imaging has been found to be helpful for assessing the ablation zone in the postprocedural setting. A recent study demonstrated that 2D imaging of the ablation zone in porcine livers may underestimate its size, and that 3D imaging with volumetric measurements may be of benefit [25]. This ability improves accuracy and allows the operator to ablate, in the same session, areas that may not have the desired ‘ablation margin’.…”
Section: Imaging Hccsmentioning
confidence: 99%
“…Für eine niedrige Lokalrezidivrate ist die genaue Kenntnis der durch das ausgewählte RFA-System induzierten Nekrose wichtig. Die Größen und Formen der induzierten Nekrosen unterscheiden sich wesentlich und müssen für die Platzierung des Applikators berücksichtigt werden [14,15]. Hierbei täuschen einzelne zweidimensionale Schnitte ein größeres therapeutisch nutzbares Volumen vor, als es sich in volumetrischen dreidimensionalen Analysen ergibt.…”
Section: Stippelunclassified